Unfair Terms in Insurance Contracts - Haykyants, A.; Khachatryan , M. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The main features of adhesion contracts are discussed in the article presented. Referring to insurance contracts formulated in standard terms, it is substantiated that such contracts are also adhesion contracts. It was also proposed to apply the regulation intended for adhesion contracts to insurance contracts formulated in standard terms. The authors characterize the criteria that the conditions must meet to be considered unfair. A new regulation is also proposed, which allows the insured (beneficiary) to demand the unfair term not to be applied to him/her.